Two new Eugenia species (Myrtaceae) from the Brazilian Atlantic forest - Giaretta, Augusto; Fraga, Claudio Nicoletti De (Phytotaxa, 2014)
Two new species of Eugenia (Myrtaceae), endemic to the Atlantic forest in the state of Espírito Santo, Brazil, are described. Eugenia amorimii has fruits with brown mealy indumentum and is similar to E. multicostata, while Eugenia sobraliana has a characteristic pedicels exfoliating longitudinally after anthesis and is similar to E. sessiliflora. The new species are restricted to single localities in the central and northwestern regions of Espírito Santo. According to the criteria of the IUCN Red List of endangered plant species both species should be considered as “Vulnerable”.